Slang Expressions in "The Greasy Strangler" Movie - Venesia Vergie; Sang Ayu Isnu Maharani; Ni Wayan Sukarini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The research titled "Slang Expressions in 'The Greasy Strangler'" explores the various slang expressions used in the movie. It aims to identify the types and meanings of these slang expressions. The study employs four methodologies: identifying the data source, collecting data from the movie transcript, analyzing the data using descriptive qualitative methods and slang dictionaries, and presenting the findings. Key findings reveal the presence of both primary and secondary slang types, as well as a range of meanings including conceptual, connotative, social, affective, reflected, and collocative meanings. The research concludes with 16 instances of slang expressions, categorized according to Chapman's theory and Leech's types of meaning.